Atypical segmental vitiligo. Late diagnosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 2-year-old child was first observed due to the presence of white spots on the right leg. The lesions were present since birth and the history was confirmed by a photo passed down from his parents (Fig. 1). They persisted unchanged from the onset. There were no other hypochromic lesions elsewhere, nor white tufts of hair. The physical examination highlighted on the right leg two white spots which occupied a large part of the front surface of the leg, with jagged edges. The precocity and fixity of the lesions led us to the clinical diagnosis of nevus depigmentosus. We saw again the child at the age of 4 years. The lesions were unchanged in form, but within them there were areas of follicular repigmentation (Fig. 2) forcing us to change the previous diagnosis in segmental vitiligo.